2016
DOI: 10.1371/journal.pone.0146126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Placenta Previa on Preeclampsia

Abstract: BackgroundThe correlation between gestational hypertension-preeclampsia (GH-PE) and placenta previa (PP) is controversial. Specifically, it is unknown whether placenta previa has any effect on the various types of preeclampsia (PE), and the role PP with concurrent placenta accreta (PA) play in the occurrence of GH-PE are not well understood.ObjectiveThe aim of this study was to identify the effects of PP on GH, mild and severe preeclampsia (MPE and SPE), and early- and late-onset preeclampsia (EPE and LPE). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…But the relationship between gestational hypertension and placenta previa remains controversial. A meta-analysis by Ying et al [ 22 ] revealed that patients with gestational hypertension have a reduced risk of placenta previa. In this study, no significant difference of placenta previa occurrence was observed between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…But the relationship between gestational hypertension and placenta previa remains controversial. A meta-analysis by Ying et al [ 22 ] revealed that patients with gestational hypertension have a reduced risk of placenta previa. In this study, no significant difference of placenta previa occurrence was observed between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The supply of blood and oxygen is greater when the placenta is implanted in the lower uterine segment rather than in the upper segment. Thus, hypoxemia can be improved and vascular remodeling can occur more easily [ 34 , 35 ]. Complete placenta previa often occurs with concurrent placenta accrete, and trophoblasts implant more deeply [ 36 , 37 ], which can contribute to more blood flow to the intervillous space.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences show that in pregnant women with placenta previa, women with pre-eclampsia had no higher incidence of fetal growth restriction than women without pre-eclampsia. These findings may be due to increased placenta blood supply in pregnant women with placenta previa (22).…”
Section: Discussionmentioning
confidence: 95%
“…Three studies were case-control (8,17,18), five studies were cohort (13,(19)(20)(21)(22), and one study was cross-sectional (23). The total sample size in the present meta-analysis was 752,243 participants.…”
Section: Description Of Studiesmentioning
confidence: 99%